Morphological And Histological Analysis Of Vascular Conduit Options Used For Coronary Artery Bypass Grafting - A South African Perspective - Ntuli, Sandile (Department of Human Biology, 2024)
Background: Cardiovascular disease is the leading cause of death worldwide and coronary artery disease (CAD), largely attributed to occluded coronary arteries, is the most common cardiovascular disease. Coronary artery bypass grafting (CABG) is considered the gold standard invasive intervention to treat CAD. This procedure involves grafting a blood vessel from elsewhere in the body to the affected coronary artery to bypass the site of occlusion. The vascular conduit may be obtained from various sites. CABG is one of the most effective and lasting therapies for CAD; however, an important decision for the surgeon to make is which vessel to use as a conduit. The aim of this study was to determine which conduit is the most morphometrically and histologically similar to coronary arteries. Methodology: The objectives of this study were met through a cross-sectional study design. The first approach was conducted on vascular conduits from the Department of Human Biology's donor sample, at the University of Cape Town (UCT), and angiographic images from the Cardiac Clinic, at Groote Schuur Hospital (GSH). The typical parameters of coronary arteries were measured, including the arteries of individuals with CAD, with the latter cohort necessary for purposes of establishing a standard. The parameters which were measured were: length, luminal diameter, and wall thickness (i.e. width of histological layer). A similar approach was used for the measuring the following vascular conduits: saphenous vein (SV), right and left internal thoracic artery (RITA/LITA), inferior epigastric artery (IEA), right gastro-epiploic artery (RGEA), and the radial artery (RA). The second approach involved cardiothoracic surgeons were surveyed regarding their decision-making before performing CABG surgery. A quantitative survey was circulated amongst South African cardiovascular surgeons to establish objective factors that affect vascular conduit choice. The questionnaire was composed of multiple choice and Linkert scale type questions. Results: The normal mean RCA length and diameter was 11.39±3.11 cm and 0.30±0.08 cm respectively, in males. For females the RCA length and diameter was 12.61±2.78 cm and 0.26±0.07 cm. The LCX had a mean length and diameter of 8.64±2.18 cm and 0.24±1.10 cm respectively for males. In females the mean length was 9.27±2.94 cm and the diameter was 0.21±0.07 cm. The AICA had a mean length and diameter of 12.06±4.22 cm and 0.25±0.08 cm respectively in males. In females the mean length and diameter was 12.84±3.34 cm and 0.20±0.07 cm, respectively. The LITA had a longer length, relative to the RITA when compared to 4 out of 5 coronary artery types, the only exception was the AICA. The mean wall thickness of the SV is 127.97±34.99 um. The mean diameter of the SV is closely related to the RCA, LCX, PICA and AICA. The respondents of the survey were from both private and public hospitals, with experience ranging from 5 to 20+ years. The SV was preferred mostly for emergencies due to easy access, while the LITA was most preferred when used individually. Discussion & conclusion: Length variance of coronary arteries is independent from sex and age, the only mean differences are found between populations. The diameter size is affected by sex, age and the presence of a pathology. This is attributed to human variation between the different sexes and the changes on the vascular system due to progressive age. Diameter and wall thickness are the prevalent factors that affect patency while length contributes to a conduits' suitability for handling during surgery. The LITA, RA and SV are the three most suitable grafts although more work must be done to compare the patency of the RA compared to the LITA and RITA used in bilateral grafts. The RITA is similar to the RGEA but depending on the coronary artery that is occluded, one might be more suitable than the other. The IEA is the least most suitable graft.